Asymptotic Behavior of Solutions for the Belousov-Zhabotinskii Reaction Diffusion System (Journal of Partial Differential Equations, 2018)
The present paper characterizes the asymptotic behavior of the timedependenr solution of the coupled Belousov-Zhabotinskii reaction diffusion equations in relation to the steady-state solutions ot the corresponding boundary value problem. This characterization leads to an cxplicit reltionship among the various physical constants and the boundary and initial functions.